Prognostic significance of pyroptosis-associated molecules in endometrial cancer: a comprehensive immunohistochemical analysis - Ha, Seong-Chan; Park, Yeon Soo; Kim, Jisup (Frontiers in Oncology, 2024)
Introduction Endometrial cancer, the most prevalent malignancy of the female genital tract, has a concerningly poor prognosis when diagnosed in advanced stages, with limited targeted therapy options available for advanced or recurrent cases. Pyroptosis, a type of nonapoptotic cell death mediated by caspase-1, has shown potential antitumor effects in various tumors. NLRP3, a cytosolic sensor, initiates the canonical pyroptotic pathway, leading to caspase-1 activation, subsequent gasdermin D cleavage, and plasma membrane pore formation. The ESCRT-III machinery, particularly CHMP4B, acts as a key inhibitor of pyroptosis by repairing gasdermin D-induced membrane damage. The current study aimed to evaluate the clinicopathologic relevance of key pyroptosis-associated molecules in endometrial cancer. Methods Immunohistochemistry was used to assess the expression of four pyroptosis-associated molecules (NLRP3, cleaved caspase-1 p20, cleaved gasdermin D, and CHMP4B) in 351 patients with endometrial cancer, and their associations with clinical, pathological, and survival outcomes were analyzed. Results High NLRP3 expression was significantly associated with age ≤ 50 years and premenopause. Increased cleaved caspase-1 p20 expression was associated with nonendometrioid carcinoma, Federation of Gynaecology and Obstetrics (FIGO) grade 3, and the p53 mutant pattern and was independently associated with poor recurrence-free survival (RFS) and overall survival. Increased cleaved gasdermin D expression was associated with a body mass index of >25 kg/m², FIGO grades 1–2, early FIGO stage (I–II), and absence of lymph node metastasis. High CHMP4B expression was associated with nonendometrioid carcinoma and poor RFS. Cleaved gasdermin D-high/CHMP4B-low endometrial cancer was associated with endometrioid carcinoma, FIGO grades 1–2 and favorable RFS. Discussion Our study identified cleaved caspase-1 p20 as an independent predictor of adverse outcomes in endometrial cancer. CHMP4B, an inhibitor of pyroptosis, was associated with an unfavorable RFS, whereas high cleaved gasdermin D/low CHMP4B expression was associated with a favorable RFS. These findings underscore the prognostic significance of pyroptosis and the potential interaction between cleaved gasdermin D and CHMP4B in endometrial cancer.